Pelatihan Bahasa Inggris dengan Altissia untuk Meningkatkan Daya Jual Agrowisata di Kawasan Desa Wisata Lembang Bandung Jawa Barat - Yulian Purnama; Bambang Suwarno (SABA JAYA PUBLISHER, 2023)
English Language Training with Altisia to Increase the Selling Power of Agrotourism in the Lembang Village Area Bandung is a new breakthrough in offering valuable assets that can be utilized by the village government in accelerating the welfare of the village community. The utilization of these assets cannot be separated from English communication competence. This competency has an impact on the quality of tourist services, especially foreign tourists. This service activity aims to help increase the selling power of agro-tourism in the Lembang Bandung Village area and awareness of the essence of hospitality from the Meler village tourism actors totaling 20 people. The service was carried out in the traditional house of Meler village and the tourist lodge of Meler tourist village for four months (March - June 2023), once a week. The methods used to achieve these objectives were lectures, questions and answers, discussions, role plays, demonstrations and personal presentations. The results showed that the trainees understood the role of hospitality in tourism services and improved fluency in tourism English communication.